Green Marketing and Consumer Attitude to Repurchasing Interest - Reni Anggraeni; Muhammad Aqsa; M. Risal (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to analyze the effect of green marketing and consumer attitudes on the intention to repurchase KFC in Palopo City. This study uses primary data and data collection techniques using questionnaires. the number of samples used in this study was 97 samples. The data analysis technique used is multiple linear regression and processed using SPSS. The results of this study indicate that simultaneously or jointly the green marketing variable and consumer attitudes have an effect on the variable of repurchasing interest. In addition, partially, the green marketing variable has a positive and significant effect on the interest in buying back KFC in Palopo City and the consumer attitude variable has a positive effect on the interest in buying back KFC in Palopo City.